THE EFFECT OF HOLDING TIME VARIATIONS IN THE AUSTENITIZATION AND SPHEROIDIZING ANNEALING PROCESSES ON THE MECHANICAL PROPERTIES AND MICROSTRUCTURE OF 304 STAINLESS STEEL THIN FOIL - Aziz, Abdul (Jurnal Rekayasa Mesin, 2025)
This study discusses the effect of holding time variations in the austenitization and spheroidizing annealing processes on the mechanical properties (hardness and tensile strength) and microstructure of 304 thin foil stainless steel materials. The austenitization process was carried out at a temperature of 900°C using holding time variations of 20, 40 and 60 minutes, followed using water. Furthermore, the spheroidizing annealing process was carried out at a temperature of 810°C with holding time variations of 200, 220 and 240 minutes and continued with tempering at a temperature of 400°C with a holding time of 60 minutes on all samples. The analysis includes hardness testing, tensile testing and microstructure observation using an optical microscope. The test results show that increasing the holding time during austenitization increases the homogeneity of austenite but can cause excessive grain growth. In contrast, the spheroidizing annealing process produces a more uniform distribution of spherical carbides and increases the ductility of the material. Then the phase formed as a result of the heat treatment process is the austenite phase as the main phase and there is martensite. Thus, this study contributes to understanding the relationship between heat treatment parameters such as holding time and mechanical properties of the material.